2012
DOI: 10.1007/s12011-012-9376-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Chloride Exposure on the Membrane Potential and Cytosolic Free Calcium in Primary Cultured Chicken Hepatocytes

Abstract: This study was conducted to examine the effects of copper on membrane potential and cytosolic free calcium in isolated primary chicken hepatocytes which were exposed to different concentration of Cu(2+) (0, 10, 50, 100 μM) or a mixture of Cu(2+) and vitamin C (50 and 50 μM, respectively). Viability, membrane potential, and cytosolic free Ca(2+) of monolayer cultured hepatocytes were investigated at the indicated time point. Results showed that, among the different concentrations of Cu(2+) exposure, the viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Additionally, the disturbance in mitochondria has a variety of harmful consequences, including energy shortage, oxidative stress, accumulation of triglycerides and cell death. A previous study also indicated that the toxicity of copper decreases mitochondrial respiration that induces apoptosis, and these findings support recent study that the degradation of mitochondria leads to overwhelming results (Jia et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the disturbance in mitochondria has a variety of harmful consequences, including energy shortage, oxidative stress, accumulation of triglycerides and cell death. A previous study also indicated that the toxicity of copper decreases mitochondrial respiration that induces apoptosis, and these findings support recent study that the degradation of mitochondria leads to overwhelming results (Jia et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Copper overload produces liver cirrhosis, neurodegeneration, and anemia mostly via the exacerbation of hydroxyl radical production by the Fenton and Haber-Weiss reactions. Copper toxicity decreases mitochondrial respiration and induces apoptosis (Medeiros and Jennings 2002;Su et al, 2011;Jia et al, 2012). On the other hand, Menkes disease features mutations in the transporter ATP7A which affect the release of copper from the enterocyte to the bloodstream, causing a severe copper deficiency that in most of cases results in death due to CIV and SOD1 dysfunction (Rossi et al, 2004;Horn and Barrientos 2008;Kim et al, 2008;Turski and Thiele 2009).…”
Section: Introductionmentioning
confidence: 99%